Understanding the Pathways to Above-Mandatory Severance Pay When Downsizing: A Qualitative Comparative Analysis of 20 Cases in France - Garaudel, Pierre; Beaujolin, Rachel; Noël, Florent; Schmidt, Géraldine (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
When it comes to negotiating over a collective dismissals plan, the French national legal framework explicitly encourages social partners to favour outplacement services over significant indemnity payments. However, significant above-mandatory redundancy payments are commonly granted to laid-off workers. Based on these factual observations, this article aims to identify the antecedent conditions, or, more precisely, the combinations of conditions, that lead to the granting of a large severance pay. We conducted a qualitative comparative analysis (Crisp set QCA) methodology applied to 20 monographs on downsizing operations that took place in France during the 2000s. The results show that above-mandatory severance payments are closely related to two major dimensions characterizing the economic and social context in which restructuring processes are carried out. The first one is about the balance of power prevailing between the company decisionmakers and the employees. This balance of power dimension is subsumed by two distinct conditions: the availability of financial resources and the presence of active unions. The second dimension relates to the moral and economic damages inflicted upon laid-off workers. This dimension is intrinsically connected to two downsizing process features, i.e. the perceived degree of legitimacy associated with the downsizing process and the degree of employability associated with the laid-off workers. Most notably, it appears that none of the identified conditions is sufficient by itself to induce the payment of a significant above-mandatory indemnity. However, some causal conditions may induce the outcome variable when they are combined with some specific other antecedent conditions. Thus, our research shows that the financial resource condition leads to the granting of an above-mandatory indemnity either in conjunction with a low degree of worker’s employability or in conjunction with both a weak perceived legitimacy of the restructuring process and the presence of active unions.